Tarjīḥ Hadis dalam Dialektika Zaman: Kajian Sistematis atas Evolusi Metodologi dan Relevansi Praktis di Era Kontemporer - Fahmi, Muhammad Zainul Arif; Bramasta, Mohammad Faqih (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2023)
This article explores the evolving academic landscape of Tarjīḥal-Hadith studies by examining the patterns, objectives, forms, and methodologies that have characterized scholarly discourse between 2012 and 2023. Responding to the fragmented understanding of contradictory hadiths (mukhtalif al-ḥadīth), the study investigates how tarjih—the method of preference—is developed and employed to address textual conflicts within prophetic traditions. Utilizing the Systematic Literature Review (SLR) method, the authors critically analyzed 16 selected publications to identify dominant trends and scholarly responses. The findings reveal that early studies largely emphasized conceptual definitions and classical reiterations of tarjih, whereas recent works began to engage contemporary issues, including digital misinformation and pandemic-related challenges. The study also uncovers a recurring stagnation in epistemology and orientation, as many contributions remain trapped in descriptive traditions rather than analytical innovation. Nevertheless, a positive shift is observed from 2021 onwards, as some scholars began integrating tarjīḥinto real-life contexts, positioning it as a relevant interpretive and legal tool in contemporary Islamic thought. The research concludes that for tarjīḥto remain intellectually and practically significant, it must transcend repetitive theorization and be continuously adapted to respond to emerging socio-religious realities. This marks a necessary transition from textual preservation to contextual activation of hadith interpretation.